THE EFFECT OF MARKETING CONTENT AND E-WOM ON THE TIKTOK APPLICATION ON PURCHASE DECISIONS STUDY ON STREET BOBA CONSUMERS IN TANGERANG CITY - Rauf, Abdul; Sulasnawati, Asri; Haromain, Achmad (Universitas Muhammadiyah Tangerang, 2024)
This study aims to analyze the effect of content marketing (X1) and e-WOM (X2) on purchasing decisions (Y) on Street Boba products (studies on consumers in Tangerang City). This research is quantitative research and survey research. The samples taken in this study were 102 respondents. Data was obtained from distributing questionnaires. Primary data processing uses ms. excel and Statistical Package For Social Science (SPSS) version 26 as evaluation. While the data analysis used in this study includes: instrument tests, classical assumption tests, multiple linear analysis, correlation analysis, and hypothesis testing. The results of this study indicate that the variables Marketing Content (X1) and E-WOM (X2) have a positive and significant influence on Purchasing Decisions as evidenced by the results of the study where in the coefficients table the sig value is 0.000 <0.1 and the F hitung value is 150.626 > F table 2.36.